2022
DOI: 10.47678/cjhe.v52i1.189453
|View full text |Cite
|
Sign up to set email alerts
|

Stress Testing the University Fall Break Policy: Understanding the Impact on Student Mental Health

Abstract: Attempting to support student mental health, many Canadian universities have implemented a fall break with the assumption it would be helpful in alleviating students’ stress and anxiety. However, there is no baseline data regarding stress level or mental illness burden of students to understand its effectiveness. Using case study methodology with mixed methods, this research sought to appraise, given a lack of baseline data, the impact of a fall break on student mental health. While the surveys revealed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…While this indicates that a university-wide fall break policy does not improve students' mental health and wellbeing, the absence of control groups and the use of between-subjects analysis urge caution. The remaining quantitatively-oriented study found no significant changes (Pilato, et al, 2022).…”
Section: Changes To Student-focused Policymentioning
confidence: 81%
See 2 more Smart Citations
“…While this indicates that a university-wide fall break policy does not improve students' mental health and wellbeing, the absence of control groups and the use of between-subjects analysis urge caution. The remaining quantitatively-oriented study found no significant changes (Pilato, et al, 2022).…”
Section: Changes To Student-focused Policymentioning
confidence: 81%
“…The 18 studies included one randomised controlled trial (RCT; Damião Neto, et al, 2020), five quasi-experimental (Ahmad, et al, 2017;Dyrbye, et al, 2017;Maynor, et al, 2022;Mc Sharry & Timmins, 2016;Poole, et al, 2018), three qualitative (Agnew, et al, 2019;Bosse, et al, 2021;McArthur, et al, 2021), and nine mixed-methods (Culver, et al, 2021;Dewa, et al, 2020;Gan, et al, 2022;Johnson, et al, 2019;Litchke, et al, 2020;Pilato, et al, 2022;Poole, et al, 2017;Wang & Du, 2020;Whiteside, et al, 2017).…”
Section: Study Types and Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end, while the fall break policy was brought forth as a recommendation by USAC, it was Senate's decision whether to maintain the break and how to implement it. Consequently, these implementation barriers (Howlett et al, 2009) ultimately had an impact on students' perceptions of the effectiveness of the break (Pilato et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, evidence-based decisions are important to implementation success or failure and should be considered as part of the evaluation process (Howlett et al, 2009). As the policy naturally progresses so can decision makers change, students change and campus climate can change with a new shifting focus on mental wellness initiatives, over time, new implementation issues may arise and so implementation will need to progress with policy changes (Pilato et al, 2021a(Pilato et al, , 2021b.…”
Section: Policy Implicationsmentioning
confidence: 99%